A preparation method and application of doped manganese precursor

By using nickel, manganese and biphenyltetracarboxylic acid in the manganese-based positive electrode material to form the MOF framework, and by doping design of butyl orthosilicate and [3-(trimethoxysilyl)propyl]succinic anhydride to form a chelated silicone structure, the problems of dissolution of active substances and silicon doping inhomogeneity of manganese-based positive electrode material are solved, and a manganese-based positive electrode material with high electrochemical performance is achieved.

CN119285986BActive Publication Date: 2025-04-11HUNAN SHUANGFU NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411804200.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-04-11
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The manganese-based positive electrode material dissolves the active substance during the charge and discharge process, resulting in poor circulation performance. The silicon-doped manganese precursor has silicon agglomeration and doping inhomogeneity problems, which affects the rate performance and capacity attenuation of the material.

Method used

The metal organic framework (MOF) is formed by coordination of nickel, manganese and 3,3',5,5'-biphenyltetrachloric acid, and then the chelated silicone structure is formed by synergistically acting with butyl orthosilicate and [3-(trimethoxysilyl)propyl]succinic anhydride, and doped into the MOF-type manganese precursor framework to prepare a doped manganese precursor.

Benefits of technology

The electrochemical performance of manganese-based cathode material is significantly improved, including high first discharge specific capacity, Coulomb efficiency up to more than 90%, excellent cycle stability and rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of electrode materials, and in particular to a preparation method and application of a doped manganese precursor. The present invention uses nickel acetate tetrahydrate and manganese acetate tetrahydrate as metal sources, 3,3',5,5'-biphenyltetracarboxylic acid as organic ligands, butyl orthosilicate and [3-(trimethoxysilyl)propyl] succinic anhydride as dopants, and constructs a doped manganese precursor through a hydrothermal reaction. The battery obtained by using the positive electrode material prepared by the doped manganese precursor of the present invention has a high first discharge specific capacity, a coulombic efficiency of more than 90%, and has extremely excellent cycle stability and rate performance, and has important application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrode materials, and in particular to a preparation method of a doped manganese precursor and application thereof. Background Art

[0002] Manganese-based cathode materials are widely used in the development of lithium-ion batteries due to their low cost, abundant resources and high specific capacity. However, in practical applications, the electrochemical performance of manganese-based materials still has certain limitations. Manganese-based materials usually need to be synthesized and regulated with appropriate precursors to ensure high performance output of cathode materials.

[0003] The microstructure, composition uniformity and surface chemical properties of manganese precursors directly determine the electrochemical performance of manganese-based cathode materials. The following problems are prone to occur in the preparation process of traditional manganese-based precursors: the skeleton of manganese precursors is prone to collapse during the subsequent preparation of cathode materials, resulting in the dissolution of active substances in the prepared manganese-based cathode materials during the charge and discharge process, which in turn affects the cycle performance. In addition, the manganese precursors have uneven particle sizes or severe agglomeration, which will reduce the specific surface area of ​​the material, hinder the insertion and deinsertion of lithium ions, and lead to rate performance and capacity attenuation.

[0004] In recent years, studies have found that the physical and chemical properties of manganese precursors can be effectively improved through doping design. In particular, the introduction of silicon doping technology can optimize the microstructure of the precursor, thereby significantly improving the electrochemical performance of the subsequent manganese-based cathode materials. However, in traditional silicon doping technology, silicon agglomeration and doping inhomogeneity are more prominent, which may lead to problems such as material pore blockage, active site embedding, and limited ion diffusion. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a preparation method of a doped manganese precursor and application thereof, so as to solve the problems of silicon agglomeration and doping non-uniformity existing in silicon-doped manganese precursor.

[0006] Based on the above purpose, the present invention provides a method for preparing a doped manganese precursor, comprising the following steps:

[0007] (1) Add nickel acetate tetrahydrate and manganese acetate tetrahydrate into anhydrous ethanol and stir for 10-30 minutes to obtain liquid A;

[0008] (2) Add 3,3',5,5'-biphenyltetracarboxylic acid into an aqueous sodium hydroxide solution and stir for 10-30 minutes to obtain solution B;

[0009] (3) Add butyl orthosilicate and [3-(trimethoxysilyl)propyl]succinic anhydride to ethylene glycol and stir for 20-40 minutes to obtain liquid C;

[0010] (4) Add liquid B and liquid C to liquid A at the same time. After the addition is completed, stir for 2-4 hours, transfer to a reactor, perform hydrothermal reaction, wash, centrifuge, and dry to obtain a doped manganese precursor.

[0011] Preferably, the molar ratio of nickel acetate tetrahydrate, manganese acetate tetrahydrate and 3,3',5,5'-biphenyltetracarboxylic acid is 1:3:2.

[0012] Preferably, the molar ratio of nickel acetate tetrahydrate, butyl orthosilicate and [3-(trimethoxysilyl)propyl]succinic anhydride is 10:0.5-1.5:0.05-0.2.

[0013] Preferably, the usage ratio of anhydrous ethanol and nickel acetate tetrahydrate is 8-12 mL:1 mmol.

[0014] Preferably, the concentration of the sodium hydroxide aqueous solution is 1-1.5 mol / L.

[0015] Preferably, the dosage ratio of the sodium hydroxide aqueous solution to 3,3',5,5'-biphenyltetracarboxylic acid is 4-6 mL:1 mmol.

[0016] Preferably, the usage ratio of ethylene glycol to butyl orthosilicate is 8-12 mL:1 mmol.

[0017] Preferably, the temperature of the hydrothermal reaction is 110-130° C. and the time is 12-20 hours.

[0018] Preferably, the washing is performed by washing with water and ethanol 2-4 times respectively.

[0019] Preferably, the drying temperature is 75-85° C. and the drying time is 10-15 hours.

[0020] Furthermore, the present invention also provides a doped manganese precursor obtained by the above-mentioned preparation method of the doped manganese precursor.

[0021] Furthermore, the present invention also provides an application of a doped manganese precursor, which can be used to prepare a positive electrode material.

[0022] Preferably, the preparation method of the positive electrode material is as follows: add the doped manganese precursor to anhydrous ethanol, ultrasonically disperse for 10-30 minutes, then add lithium acetate dihydrate, heat to 40-60°C, stir for 4-6 hours, then dry at 65-75°C for 10-15 hours, transfer to a muffle furnace, heat to 380-420°C and sinter for 2-4 hours, then heat to 750-850°C and sinter for 10-15 hours, cool to obtain the positive electrode material.

[0023] Beneficial effects of the present invention:

[0024] The invention provides a doped manganese precursor, which forms a metal organic framework (MOF) through the coordination of nickel, manganese and 3,3',5,5'-biphenyltetracarboxylic acid, that is, a MOF-type manganese precursor skeleton, and then forms a chelated organic silicon structure through the synergistic effect of butyl orthosilicate and [3-(trimethoxysilyl)propyl]succinic anhydride, and is doped into the MOF-type manganese precursor skeleton to obtain a doped manganese precursor. A battery obtained by using the positive electrode material prepared by the doped manganese precursor of the invention has a high first discharge specific capacity, a coulombic efficiency of more than 90%, and extremely excellent cycle stability and rate performance, and has important application value.

[0025] The present invention forms a chelated organic silicon structure through the synergistic effect of butyl orthosilicate and [3-(trimethoxysilyl)propyl]succinic anhydride, and dopes it into the MOF type manganese precursor skeleton. Under the premise of not destroying its framework structure, the dissolution of active substances is effectively reduced, the stability of positive electrode materials is enhanced, and the rate performance and cycle performance of the battery prepared therefrom are improved.

[0026] The present invention adopts ethylene glycol as the solvent of siloxane, effectively regulates the hydrolysis polymerization of siloxane, avoids the generation of large particles of organic silicon, prevents the destruction of the structure of the MOF type manganese precursor and the clogging of the pores, reduces the embedding of active sites, and improves the ionic conductivity of the positive electrode material. DETAILED DESCRIPTION

[0027] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0028] Embodiment 1:

[0029] Preparation of doped manganese precursor:

[0030] (1) Add 10 mmol of nickel acetate tetrahydrate and 30 mmol of manganese acetate tetrahydrate into 80 mL of anhydrous ethanol and stir for 10 min to obtain liquid A;

[0031] (2) Add 20 mmol of 3,3',5,5'-biphenyltetracarboxylic acid into 80 mL of 1 mol / L sodium hydroxide aqueous solution and stir for 10 min to obtain solution B;

[0032] (3) Add 0.5 mmol of butyl orthosilicate and 0.05 mmol of [3-(trimethoxysilyl)propyl]succinic anhydride to 4 mL of ethylene glycol and stir for 20 min to obtain liquid C;

[0033] (4) Add liquid B and liquid C to liquid A at the same time. After the addition is completed, stir for 2 hours, transfer to a reactor, and perform hydrothermal reaction at 110°C for 12 hours. Then wash twice with water and ethanol respectively, centrifuge, and dry at 75°C for 10 hours to obtain a doped manganese precursor.

[0034] Preparation of positive electrode material: Add the doped manganese precursor prepared in step (4) into 100 mL of anhydrous ethanol, ultrasonically disperse for 20 min, then add 20 mmol of lithium acetate dihydrate, heat to 50°C, stir for 5 h, then dry at 70°C for 12 h, transfer to a muffle furnace, heat to 400°C and sinter for 3 h, then heat to 800°C and sinter for 12 h, cool to obtain the positive electrode material.

[0035] Embodiment 2:

[0036] Preparation of doped manganese precursor:

[0037] (1) Add 10 mmol of nickel acetate tetrahydrate and 30 mmol of manganese acetate tetrahydrate into 100 mL of anhydrous ethanol and stir for 20 min to obtain liquid A;

[0038] (2) Add 20 mmol of 3,3',5,5'-biphenyltetracarboxylic acid into 100 mL of 1.2 mol / L sodium hydroxide aqueous solution and stir for 20 min to obtain solution B;

[0039] (3) Add 1 mmol of butyl orthosilicate and 0.1 mmol of [3-(trimethoxysilyl)propyl]succinic anhydride into 10 mL of ethylene glycol and stir for 30 min to obtain liquid C;

[0040] (4) Liquid B and Liquid C were added dropwise to Liquid A at the same time. After the addition was completed, the mixture was stirred for 3 h, and then transferred to a reactor for hydrothermal reaction at 120 °C for 15 h. The mixture was then washed with water and ethanol for 3 times, centrifuged, and dried at 80 °C for 12 h to obtain a doped manganese precursor.

[0041] Preparation of positive electrode material: Add the doped manganese precursor prepared in step (4) into 100 mL of anhydrous ethanol, ultrasonically disperse for 20 min, then add 20 mmol of lithium acetate dihydrate, heat to 50°C, stir for 5 h, then dry at 70°C for 12 h, transfer to a muffle furnace, heat to 400°C and sinter for 3 h, then heat to 800°C and sinter for 12 h, cool to obtain the positive electrode material.

[0042] Embodiment 3:

[0043] Preparation of doped manganese precursor:

[0044] (1) Add 10 mmol of nickel acetate tetrahydrate and 30 mmol of manganese acetate tetrahydrate into 120 mL of anhydrous ethanol and stir for 30 min to obtain liquid A;

[0045] (2) Add 20 mmol of 3,3',5,5'-biphenyltetracarboxylic acid into 120 mL of 1.5 mol / L sodium hydroxide aqueous solution and stir for 30 min to obtain solution B;

[0046] (3) Add 1.5 mmol of butyl orthosilicate and 0.2 mmol of [3-(trimethoxysilyl)propyl]succinic anhydride into 18 mL of ethylene glycol and stir for 40 min to obtain liquid C;

[0047] (4) Liquid B and Liquid C were added dropwise to Liquid A at the same time. After the addition was completed, the mixture was stirred for 4 h, and then transferred to a reactor for hydrothermal reaction at 130 °C for 20 h. The mixture was then washed with water and ethanol for 4 times, centrifuged, and dried at 85 °C for 15 h to obtain a doped manganese precursor.

[0048] Preparation of positive electrode material: Add the doped manganese precursor prepared in step (4) into 100 mL of anhydrous ethanol, ultrasonically disperse for 20 min, then add 20 mmol of lithium acetate dihydrate, heat to 50°C, stir for 5 h, then dry at 70°C for 12 h, transfer to a muffle furnace, heat to 400°C and sinter for 3 h, then heat to 800°C and sinter for 12 h, cool to obtain the positive electrode material.

[0049] Comparative Example 1:

[0050] The difference between Comparative Example 1 and Example 2 is that the butyl orthosilicate in step (3) is replaced by an equal molar amount of [3-(trimethoxysilyl)propyl]succinic anhydride;

[0051] The specific steps are as follows:

[0052] Preparation of manganese precursor:

[0053] (1) Add 10 mmol of nickel acetate tetrahydrate and 30 mmol of manganese acetate tetrahydrate into 100 mL of anhydrous ethanol and stir for 20 min to obtain liquid A;

[0054] (2) Add 20 mmol of 3,3',5,5'-biphenyltetracarboxylic acid into 100 mL of 1.2 mol / L sodium hydroxide aqueous solution and stir for 20 min to obtain solution B;

[0055] (3) Add 1.1 mmol of [3-(trimethoxysilyl)propyl]succinic anhydride to 10 mL of ethylene glycol and stir for 30 min to obtain liquid C;

[0056] (4) Add liquid B and liquid C to liquid A at the same time. After the addition is completed, stir for 3 hours, transfer to a reactor, and perform hydrothermal reaction at 120°C for 15 hours. Then wash with water and ethanol three times respectively, centrifuge, and dry at 80°C for 12 hours to obtain a manganese precursor.

[0057] Preparation of positive electrode material: The manganese precursor prepared in step (4) was added to 100 mL of anhydrous ethanol, ultrasonically dispersed for 20 min, and then 20 mmol of lithium acetate dihydrate was added. The temperature was raised to 50°C, stirred for 5 h, and then dried at 70°C for 12 h. The mixture was transferred to a muffle furnace, heated to 400°C and sintered for 3 h, and then heated to 800°C and sintered for 12 h. The temperature was lowered to obtain the positive electrode material.

[0058] Comparative Example 2:

[0059] The difference between Comparative Example 2 and Example 2 is that: [3-(trimethoxysilyl)propyl]succinic anhydride in step (3) is replaced by an equal molar amount of butyl orthosilicate;

[0060] The specific steps are as follows:

[0061] Preparation of manganese precursor:

[0062] (1) Add 10 mmol of nickel acetate tetrahydrate and 30 mmol of manganese acetate tetrahydrate into 100 mL of anhydrous ethanol and stir for 20 min to obtain liquid A;

[0063] (2) Add 20 mmol of 3,3',5,5'-biphenyltetracarboxylic acid into 100 mL of 1.2 mol / L sodium hydroxide aqueous solution and stir for 20 min to obtain solution B;

[0064] (3) Add 1.1 mmol of butyl orthosilicate into 10 mL of ethylene glycol and stir for 30 min to obtain liquid C;

[0065] (4) Add liquid B and liquid C to liquid A at the same time. After the addition is completed, stir for 3 hours, transfer to a reactor, and perform hydrothermal reaction at 120°C for 15 hours. Then wash with water and ethanol three times respectively, centrifuge, and dry at 80°C for 12 hours to obtain a manganese precursor.

[0066] Preparation of positive electrode material: The manganese precursor prepared in step (4) was added to 100 mL of anhydrous ethanol, ultrasonically dispersed for 20 min, and then 20 mmol of lithium acetate dihydrate was added. The temperature was raised to 50°C, stirred for 5 h, and then dried at 70°C for 12 h. The mixture was transferred to a muffle furnace, heated to 400°C and sintered for 3 h, and then heated to 800°C and sintered for 12 h. The temperature was lowered to obtain the positive electrode material.

[0067] Comparative Example 3:

[0068] The difference between Comparative Example 3 and Example 2 is that: Liquid C is not added dropwise in step (4);

[0069] The specific steps are as follows:

[0070] Preparation of doped manganese precursor:

[0071] (1) Add 10 mmol of nickel acetate tetrahydrate and 30 mmol of manganese acetate tetrahydrate into 100 mL of anhydrous ethanol and stir for 20 min to obtain liquid A;

[0072] (2) Add 20 mmol of 3,3',5,5'-biphenyltetracarboxylic acid into 100 mL of 1.2 mol / L sodium hydroxide aqueous solution and stir for 20 min to obtain solution B;

[0073] (4) Liquid B was added dropwise to Liquid A. After the addition was completed, the mixture was stirred for 3 h, and then transferred to a reactor for hydrothermal reaction at 120 °C for 15 h. The mixture was then washed with water and ethanol for 3 times, centrifuged, and dried at 80 °C for 12 h to obtain a manganese precursor.

[0074] Preparation of positive electrode material: The manganese precursor prepared in step (4) was added to 100 mL of anhydrous ethanol, ultrasonically dispersed for 20 min, and then 20 mmol of lithium acetate dihydrate was added. The temperature was raised to 50°C, stirred for 5 h, and then dried at 70°C for 12 h. The mixture was transferred to a muffle furnace, heated to 400°C and sintered for 3 h, and then heated to 800°C and sintered for 12 h. The temperature was lowered to obtain the positive electrode material.

[0075] Comparative Example 4:

[0076] The difference between Comparative Example 4 and Example 2 is that the ethylene glycol in step (3) is replaced by anhydrous ethanol.

[0077] The specific steps are as follows:

[0078] Preparation of manganese precursor:

[0079] (1) Add 10 mmol of nickel acetate tetrahydrate and 30 mmol of manganese acetate tetrahydrate into 100 mL of anhydrous ethanol and stir for 20 min to obtain liquid A;

[0080] (2) Add 20 mmol of 3,3',5,5'-biphenyltetracarboxylic acid into 100 mL of 1.2 mol / L sodium hydroxide aqueous solution and stir for 20 min to obtain solution B;

[0081] (3) Add 1 mmol of butyl orthosilicate and 0.1 mmol of [3-(trimethoxysilyl)propyl]succinic anhydride into 10 mL of anhydrous ethanol and stir for 30 min to obtain liquid C;

[0082] (4) Add liquid B and liquid C to liquid A at the same time. After the addition is completed, stir for 3 hours, transfer to a reactor, and perform hydrothermal reaction at 120°C for 15 hours. Then wash with water and ethanol three times respectively, centrifuge, and dry at 80°C for 12 hours to obtain a manganese precursor.

[0083] Preparation of positive electrode material: The manganese precursor prepared in step (4) was added to 100 mL of anhydrous ethanol, ultrasonically dispersed for 20 min, and then 20 mmol of lithium acetate dihydrate was added. The temperature was raised to 50°C, stirred for 5 h, and then dried at 70°C for 12 h. The mixture was transferred to a muffle furnace, heated to 400°C and sintered for 3 h, and then heated to 800°C and sintered for 12 h. The temperature was lowered to obtain the positive electrode material.

[0084] Comparative Example 5:

[0085] The difference between Comparative Example 5 and Example 2 is that: Liquid C is not added in step (4), and butyl orthosilicate is added during the preparation of the positive electrode material;

[0086] The specific steps are as follows:

[0087] Preparation of manganese precursor:

[0088] (1) Add 10 mmol of nickel acetate tetrahydrate and 30 mmol of manganese acetate tetrahydrate into 100 mL of anhydrous ethanol and stir for 20 min to obtain liquid A;

[0089] (2) Add 20 mmol of 3,3',5,5'-biphenyltetracarboxylic acid into 100 mL of 1.2 mol / L sodium hydroxide aqueous solution and stir for 20 min to obtain solution B;

[0090] (3) Liquid B was added dropwise to Liquid A. After the addition was completed, the mixture was stirred for 3 h, and then transferred to a reactor for hydrothermal reaction at 120 °C for 15 h. The mixture was then washed with water and ethanol for 3 times, centrifuged, and dried at 80 °C for 12 h to obtain a manganese precursor.

[0091] Preparation of positive electrode material: The manganese precursor prepared in step (4) and 1 mmol of butyl orthosilicate were added to 100 mL of anhydrous ethanol, and ultrasonically dispersed for 20 min. Then, 20 mmol of lithium acetate dihydrate was added, and the temperature was raised to 50°C, stirred for 5 h, and then dried at 70°C for 12 h. The mixture was transferred to a muffle furnace, heated to 400°C and sintered for 3 h, and then heated to 800°C and sintered for 12 h. The temperature was lowered to obtain the positive electrode material.

[0092] Battery preparation:

[0093] Positive electrode sheet: The positive electrode materials prepared in the embodiment and the comparative example are respectively used as active materials, acetylene black is used as a conductive agent, and a 1-methyl-2-pyrrolidone solution of 4% by mass of polyvinylidene fluoride is used as a binder. The positive electrode active material, 4% PVDF, and acetylene black are weighed in a mass ratio of 75:15:10 and mixed evenly. The mixture is stirred for 6 hours at room temperature. The obtained slurry is evenly coated on a clean aluminum foil, and vacuum dried at 60°C overnight to remove the organic solvent. The positive electrode sheet is then punched with a punching machine having a punch diameter of 12 mm to obtain a positive electrode sheet.

[0094] Battery assembly: The positive electrode sheet obtained above is used as the positive electrode, the lithium sheet is used as the negative electrode, the electrolyte is a 1M LiPF6 organic solution, the solvent composition is dimethyl carbonate / diethyl carbonate / ethylene carbonate (volume ratio is 1:1:1), the diaphragm is a polypropylene film, and the assembled battery model is a 2032 button cell. The battery assembly order is positive electrode shell, positive electrode sheet, diaphragm, negative electrode sheet, negative electrode shell, a total of 6 drops of electrolyte are added, and then the battery is packaged with a battery packaging machine. The packaged battery is left to stand for 12 hours and the performance test is carried out.

[0095] Performance Testing:

[0096] Constant current charge and discharge test: The Xinwei battery testing system was used to test the charge and discharge specific capacity, cycle performance and rate performance of the batteries prepared from the positive electrode materials of the embodiments and comparative examples. The charge and discharge specific capacity at room temperature was measured using a current of 0.1C, and the cycle performance at room temperature was measured using a current of 1C. The rate performance test range was 0.1C, 0.2C, 0.5C, 1C, 2C and 10C, 5 cycles each, and the voltage test range was 2.0-4.75V. The results are shown in Table 1.

[0097] Table 1 Performance test results

[0098]

[0099] Data Analysis:

[0100] It can be seen from the data of Examples 1-3 in Table 1 that the battery prepared using the doped manganese precursor provided by the present invention has a higher first discharge specific capacity and a coulombic efficiency of more than 90%. In addition, in the rate performance test, the discharge specific capacity under the 10C rate charge and discharge conditions is still maintained at a high level, indicating that the battery has excellent rate performance. More importantly, under the 1C rate condition, after 500 cycles of cycle testing, the capacity retention rate is still above 99%, which shows that the battery prepared by the present invention has extremely outstanding cycle stability and long-life use characteristics. This is mainly due to the unique design of the doped manganese precursor, which can effectively improve the structural stability and electrochemical properties of the battery, thereby maintaining high capacity and stable performance output during long-term cycle charge and discharge.

[0101] It can be seen from the data of Example 2 and Comparative Examples 1-3 in Table 1 that butyl orthosilicate and [3-(trimethoxysilyl)propyl]succinic anhydride synergistically improve the performance of the battery, especially the rate performance and the cycle performance. This is mainly because the chelated organosilicon formed by butyl orthosilicate and [3-(trimethoxysilyl)propyl]succinic anhydride can be doped into the MOF-type manganese precursor skeleton without destroying the structure of the MOF-type manganese precursor itself, thereby helping to improve the stability of the positive electrode material, and the silicon uniformly dispersed in the positive electrode material helps to reduce the dissolution of the active substance and does not affect the ionic conductivity of the material.

[0102] It can be seen from the data of Example 2 and Comparative Example 4 in Table 1 that, compared with ethanol, ethylene glycol as a solvent for siloxane is more helpful in improving the rate performance and cycle performance of the battery. This is because ethylene glycol effectively regulates the hydrolysis and polymerization of siloxane, thereby avoiding the generation of large particles of organic silicon. Large particles of organic silicon may destroy the structure of the MOF-type manganese precursor and block the pores on the one hand, and may lead to the embedding of active sites on the other hand, affecting the ionic conductivity.

[0103] From the data of Example 2 and Comparative Example 5 in Table 1, it can be seen that the doping order of silicon has a great influence on the coulombic efficiency of the battery. This is mainly because the post-doped silicon may embed part of the active sites on the surface of the material, inhibiting the embedding and de-embedding process of lithium ions in the positive electrode material, thereby causing the efficiency of the electrochemical reaction to decrease. In addition, the post-doped silicon is prone to cause non-uniform distribution and agglomeration of silicon elements, which will further affect the microstructural characteristics of the positive electrode material, such as increasing the impedance between particles and reducing the diffusion rate of lithium ions. More importantly, post-doped silicon may significantly increase the particle size of the positive electrode material, reduce its specific surface area, thereby reducing the interfacial reaction capacity between the material and the electrolyte, and ultimately have a negative impact on the coulombic efficiency of the battery.

[0104] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A method for preparing a doped manganese precursor, characterized in that: The following steps are involved: (1) Add nickel acetate tetrahydrate and manganese acetate tetrahydrate into anhydrous ethanol and stir for 10-30 minutes to obtain liquid A; (2) Add 3,3',5,5'-biphenyltetracarboxylic acid into an aqueous sodium hydroxide solution and stir for 10-30 minutes to obtain solution B; (3) Add butyl orthosilicate and [3-(trimethoxysilyl)propyl]succinic anhydride to ethylene glycol and stir for 20-40 minutes to obtain liquid C; (4) Add liquid B and liquid C to liquid A at the same time. After the addition is completed, stir for 2-4 hours, transfer to a reactor, perform hydrothermal reaction, wash, centrifuge, and dry to obtain a doped manganese precursor. The molar ratio of the nickel acetate tetrahydrate, the manganese acetate tetrahydrate and the 3,3',5,5'-biphenyltetracarboxylic acid is 1:3:2; The molar ratio of the nickel acetate tetrahydrate, butyl orthosilicate and [3-(trimethoxysilyl)propyl]succinic anhydride is 10:0.5-1.5:0.05-0.

2.

2. The method for preparing a doped manganese precursor according to claim 1, characterized in that: The usage ratio of anhydrous ethanol and nickel acetate tetrahydrate is 8-12mL:1mmol.

3. The method for preparing a doped manganese precursor according to claim 1, characterized in that: The concentration of the sodium hydroxide aqueous solution is 1-1.5 mol / L.

4. The method for preparing a doped manganese precursor according to claim 1, characterized in that: The dosage ratio of the sodium hydroxide aqueous solution to 3,3',5,5'-biphenyltetracarboxylic acid is 4-6 mL:1 mmol.

5. The method for preparing a doped manganese precursor according to claim 1, characterized in that: The usage ratio of ethylene glycol and butyl orthosilicate is 8-12mL:1mmol.

6. The method for preparing a doped manganese precursor according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 110-130° C. and the time is 12-20 hours.

7. The method for preparing a doped manganese precursor according to claim 1, characterized in that: The washing is performed by washing with water and ethanol for 2-4 times respectively.

8. The method for preparing a doped manganese precursor according to claim 1, characterized in that: The drying temperature is 75-85°C and the drying time is 10-15h.

9. An application of a doped manganese precursor, characterized in that: The doped manganese precursor is obtained by the method for preparing a doped manganese precursor according to any one of claims 1 to 8, and is used to prepare a positive electrode material.

Citation Information

Patent Citations

  • Ternary positive electrode material and preparation method and application thereof

    CN112670482A

  • Doped and coated composite modified lithium nickel manganese oxide positive electrode material and preparation method thereof

    CN116404168A